Aba Ginoong Maria [videorecording] the great virgins of Luzon - Medina, Susan Calo.; Quintos, Floy.; GMA 7 (Television station : Quezon City, Philippines).; Philippines. Department of Tourism; Travel Time (Television program). (Manila Travel Time, 1996)
A documentary on the great Virgins of Luzon. It presents the Blessed Virgin Mary's historical significance, her role and importance of Filipino culture. It features the virgins of La Naval, De Guia, Dela Paz de Buenviaje and Penafrancia.
Documentary.
VHS.
Keywords: Mary, Blessed Virgin, Saint -- Feasts; Festivals -- Philippines -- Luzon; Rites and ceremonies -- Philippines -- Luzon